2008
DOI: 10.1186/1471-213x-8-97
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Oct-4 is a potential key regulator of the developmental competence of mouse oocytes

Abstract: Background: The maternal contribution of transcripts and proteins supplied to the zygote is crucial for the progression from a gametic to an embryonic control of preimplantation development. Here we compared the transcriptional profiles of two types of mouse MII oocytes, one which is developmentally competent (MII SN oocyte), the other that ceases development at the 2-cell stage (MII NSN oocyte), with the aim of identifying genes and gene expression networks whose misregulated expression would contribute to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 63 publications
4
49
1
Order By: Relevance
“…A total of 123 antral oocytes isolated from the ovaries of four females were analysed by immunocytochemistry, 49 (39.8%) and 74 (60.2%) of them owned an NSN-or SN-type of chromatin organisation, respectively, confirming frequencies previously reported [24,27]. This analysis, demonstrated the presence of the acetylated form of the three histones in all the oocytes observed (AcH3: 43 oocytes analysed; AcH2B: 37; AcH4: 43).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…A total of 123 antral oocytes isolated from the ovaries of four females were analysed by immunocytochemistry, 49 (39.8%) and 74 (60.2%) of them owned an NSN-or SN-type of chromatin organisation, respectively, confirming frequencies previously reported [24,27]. This analysis, demonstrated the presence of the acetylated form of the three histones in all the oocytes observed (AcH3: 43 oocytes analysed; AcH2B: 37; AcH4: 43).…”
Section: Resultssupporting
confidence: 80%
“…When the expression of one of the 27 maternal-effect factors identified so far is altered, mouse embryos arrest development, mostly at the 2-cell stage (for a review see [13]). We have recently shown that one of the possible causes of the developmental incompetence of MII NSN oocytes is the down-regulation of two maternaleffect factors, OCT4 and STELLA [27,28], required for development beyond the 2-cell stage [8,20].…”
Section: Introductionmentioning
confidence: 99%
“…From recent investigations, it has also emerged that Sox2 is one of the transcription factors underlying the derivation of induced pluripotent stem cells [2]. Maternal Sox2 RNA and protein, as for Oct4 [3], are present in fertilized oocytes until the two-cell stage. Zygotic Sox2 RNA, during embryogenesis, is expressed in the morula at 2.5 days postcoitum (dpc), inner cell mass of the blastocyst from 3.5 dpc and, at a later stage, in epiblast cells [4].…”
Section: Introductionmentioning
confidence: 99%
“…With a similar aim, MII developmentally competent oocytes (MII SN ) were compared with oocytes that cease development at the 2-cell stage (MII NSN ) , Zuccotti et al, 2008. The GO enrichment analysis performed with DAVID and the networks obtained using IPA allowed the identification of gene expression networks involved into the regulation of biochemical pathways representative of the adverse biological status of MII NSN oocytes.…”
Section: Applications To -Omics Analysis In Oogenesis and Early Embrymentioning
confidence: 99%